Corporate reporting on corruption: An international comparison. Issue 4 (December 2015) - Barkemeyer, Ralf; Preuss, Lutz; Lee, Lindsay
Highlights: We explore anti-corruption disclosures as part of corporate sustainability reports. We identify country- and sector level differences in anti-corruption reporting. However, companies that are at greater risk of corruption report less on the issue. Participation in anti-corruption initiatives has a positive impact on reporting. Our results cast doubt on the usefulness of voluntary anti-corruption disclosures. Abstract: Building on an institutionalist framework of the various organizational field-level pressures on firms to engage with the challenge of corruption, we analyse anti-corruption disclosures across a sample of 933 sustainability reports. Such reporting complements anti-corruption initiatives, as it allows the company to demonstrate its commitment. Our results show clear country- and sector-level differences in the extent to which companies communicate their anti-corruption engagement. However, the more a company is exposed to corruption, the less likely it appears to openly communicate its anti-corruption engagement. Hence, our results cast doubt on the effectiveness of anti-corruption disclosures as part of wider sustainability reporting.